Efektivitas Pengaturan Penggunaan Life Jacket Dalam Menunjang Keselamatan Berlayar Di Pelabuhan Sanur - Putu San Saniago; Made Hendra Wijaya (Jurnal Hukum Mahasiswa, 2026)
Maritime safety is a fundamental aspect of sea transportation activities that must be fulfilled by every ship operator and passenger. One of the key instruments in ensuring safety at sea is the use of life jackets, as stipulated in Article 1, Number 32 of Law Number 66 of 2024 concerning Shipping, which states that lifesaving equipment, including life jackets, constitutes mandatory safety gear that must be available, in good condition, and easily accessible to passengers. This study aims to determine the level of implementation of life jacket usage regulations at Sanur Port and to identify the factors that hinder their enforcement. The research employs a juridical-empirical method with a qualitative approach, involving interviews and observations with ship operators, passengers, and port officers. Secondary data were obtained through a literature review of relevant laws and maritime safety regulations. The findings indicate that the implementation level of life jacket usage regulations at Sanur Port remains suboptimal, as evidenced by passengers’ low awareness, weak supervision by officers, and the limited quantity and quality of available life jackets. Therefore, enhanced public awareness campaigns, stricter supervision, and stronger law enforcement are required to ensure that the application of Article 1, Number 32 of Law Number 66 of 2024 is effective in supporting maritime safety at Sanur Port.